COVID-19 Mortality and the Cytokine Storm: An Added Value for APOE Genotyping - Diambra, Luis Anibal (2022)
The new COVID-19 presents some comorbidities, such as obesity, Alzheimer’s, and coronary risk, among others. We argue that the current understanding of some of these clinical conditions may illuminate the design of future COVID-19 studies to account for a bias that may be the cause of the para-doxical associations between COVID-19 mortality and cytokine storm. Given that we know some of the genetic mechanisms behind these diseases, it is possible to circumscribe these studies to some key genes that help us understand why some patients experience a cytokine storm and what the treatment strategies might be. In this paper, we discuss the role of A2M and APOE genes. A2M encodes a multifaceted protein which is highly expressed in the liver and released to the bloodstream associated with the apolipopro-tein E. This association depends on the APOE genotype. A2M has protease-clearing activity binding of a broad range of proteases, such as thrombin and Factor Xa. It also presents the ability to bind to proin-flammatory ligands, like cytokines. Further, A2M acts as chaperone of misfolded substrates, like beta-amyloid peptide. The last two molecular functions grant it a key role in regulating both inflammatory processes, as well as extracellular protein homeostasis. For these reasons, we conclude that A2M-APOE association will have prophylactic, therapeutic, and prognostic implications; and the proper understanding of the physiological role of APOE and A2M in controlling inflammatory processes can shed further light on the putative treatment of COVID-19-derived cytokine storm.